WORKING FROM HOME: WOMEN BETWEEN PUBLIC AND DOMESTIC SPHERES AFTER THE OUTBREAK OF COVID-19 - Elfira, Mina; Wibawarta, Bambang; Esther, Rouli; Febriand, Fandra (International Review of Humanities Studies, 2021)
This study examines how working mothers negotiate her gender role and strategize in facing the condition when domestic and public sphere exist in one space called home after the outbreak COVID-19 pandemic in Indonesia. The research questions are ” how far does working from home give an impact in changing patriarchal gender relation and distribution of work division at home?”, and “to what extends women modify their home functions in coping with COVID 19 pandemic condition and in minimizing patriarchal authority at their own home?” The research uses qualitative methods, including in-depth interviews and questioner filling, and focuses on samples of 30 middle class working women, living in Jabodetabek (Jakarta, Bogor, Depok, Tangerang, Bekasi) area. This study argues that as the impact of Covid pandemic condition, the middle class working mothers, who have been “forced to go back” to their homes, seemingly, use their homes as “struggling places” to renegotiate the old patriarchal role divisions and unequal gender/power relations. Moreover, it is argued that their homes, to some extends, are used as learning sites for gender equality values, and modified to fulfill their extended functions: as domestic, work, and social spheres.